Associations between With-The-Rule and Against-The-Rule Astigmatism and Higher-Order Aberrations in Compound Myopic Astigmatism: Doi: 10.36351/pjo.v41i2.2010 - Mohaghegh, Sahar; Kangari, Haleh; Bamdad, Shahram; Rahmani, Saeed (Pakistan Journal of Ophthalmology, 2025)
Purpose: To examine the relationship between astigmatism axis and higher-order aberrations (HOAs) in patients with compound myopic astigmatism. Study Design: Cross-sectional descriptive study. Place and Duration of Study: Cornea Clinic in the Shiraz University of Medical Science, Shiraz, Iran, from 2018-2020. Methods: A total of 1370right eyes, aged 18-40 years, were included in the study. Subjective cycloplegic refraction and distance aberrometry, measured with a Shack-Hartmann device, were analyzed. Zernike components of horizontal coma(Z31), vertical coma(Z3-1), oblique trefoil(Z33), vertical trefoil(Z3-3), spherical aberration, and total root-mean-square wave-front errors for 6 mm pupils were analyzed. With the rule and against the rule astigmatism groups were defined based on vector analysis for the astigmatism axis (J0 and J45). Positive and negative values of J0 indicate with-the-rule and against-the-rule astigmatism, respectively. Spearman’s correlations were calculated between HOAs and J0.(To simplify evaluation, we did not consider J45 in analysis which indicates oblique astigmatism). Results: The mean age was 29.01±5.19. The mean spherical equivalent (SEQ) was -3.64 ± 1.59D, range [-0.75 to -10.00 D] and the mean cylindrical power was -1.01 ± 0.95D, range [0 to -5.00D]. J0 correlates positively with vertical coma(Z3-1) (r = 0.1 p <0.001) and negatively with oblique trefoil(Z33), (r = -0.1, p < 0.001). Conclusion: We found weak systematic correlations between third-order aberrations and the astigmatism axis. Increasing against-the-rule is associated with a positive shift in oblique trefoil(Z33) and a negative shift in vertical coma(Z3-1).